Two modes of being together: The levels of intersubjectivity and human relatedness in neuroscience and psychoanalytic thinking - Williams, Riccardo; Trentini, Cristina (Frontiers in Human Neuroscience, 2022)
The notion of inter-subjectivity has achieved a primary status in contemporary psychoanalytic debate, stimulating new theoretical proposals as well as controversies. This paper presents an overview of the main contributions on inter-subjectivity in the field of neurosciences. In humans as well as—probably—in other species, the ability for emotional resonance is guaranteed early in development. Based on this capacity, a primary sense of connectedness is established that can be defined inter-subjective in that it entails sharing affective states and intentions with caregivers. We propose to define such a form of inter-subjectivity as contingent, since the infant’s early abilities for resonance do not imply the more generalized capacity to permanently conceive of the relationship outside the realm of current interactions and the infant-caregiver’s mutual correspondence of internal states. This form of connection, hence, results in a self-referential, bodily, and affectively codified, context- and time dependent, like-me experience of interactions. The gradual maturation of brain structures and processes as well as interactive experiences allow proper inter-subjective exchanges, grounded on new intentional and representational capacities, to evolve. In this more mature form of intersubjectivity, the individual is allowed to conceive of her own psychic space both as distinct and as possibly connected with the other’s contents and experience, even in the absence of current behavioral indicators of such correspondence. This multi-layered model of inter-subjectivity, which is embraced by current neuro-scientific research, seems to allow for new interpretations of psychoanalytic models of human relatedness based upon classic clinical observations.